PEMBELAJARAN SEJARAH DI ERA REVOLUSI INDUSTRI 4.0 - Dewa Agung Gede Agung (Universitas Negeri Malang, 2021)
Industrial Revolution 4.0 influences historical learning both in substance and in the learning process. This development starts from materials, methods, media, innovative learning models, and especially substances that often cause controversy. The development of technology causes a variety of historical information easily obtained. History lessons should follow these developments, although not all of them have a positive impact on students, history teachers, and historians. They must be able to be selective in responding to various developments in the availability of historical information. Collaboration and elaboration between history and other fields of science are necessary to see various changes and developments in society. History needs to be viewed in a multiperspective manner rather than a mono perspective. Thus, the learning history will provide comprehensive and integrated information that produces the total history. Therefore, this paper provides an alternative way of learning history in the Era of Industrial Revolution 4.0.